Analisis Permasalahan Pembelajaran di Sekolah Dasar pada Abad 21: Suatu Tinjauan Filosofis, Pedagogis, Sosio Kultural, dan Psikologis Melalui Pendekatan Berdiferensiasi - Herdi Pangkey, Richard Daniel; Asari Lengkong, Afrilia; Leonita Horman, Meisara; Ritsita Lengkong, Gloria (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2025)
The problems of learning in primary schools in the 21st century have become increasingly complex, influenced by philosophical, pedagogical, socio-cultural, and psychological factors. From a philosophical perspective, education tends to be reduced to pragmatic academic goals, obscuring its essence as a process of humanization and character formation. Pedagogically, challenges arise from the gap in teachers’ competencies in dealing with digital-native learners who demand interactive, collaborative, and creative learning experiences. From a socio-cultural standpoint, globalization and technological advancement create a paradox—on the one hand, they expand access to information, but on the other hand, they can weaken local cultural identity and widen regional disparities. Psychologically, elementary students face pressures from academic demands, limited emotional support, and the negative effects of excessive gadget use. To address these issues, a differentiated teaching approach serves as a strategic alternative that aligns learning processes with students’ readiness, interests, and learning profiles. Through the integration of Lower Order Thinking Skills (LOTs) and Higher Order Thinking Skills (HOTs), this approach not only strengthens cognitive competence but also fosters students’ critical, creative, and reflective thinking in accordance with 21st-century learning demands. Thus, a multidimensional analysis combining the four perspectives and differentiated instruction underscores that solutions to elementary education challenges must be holistic, adaptive, and contextually grounded, enabling the formation of learners who are academically competent, psychologically healthy, and culturally rooted.